Continuous Lumbar Plexus Block: Use of Radiography to Determine Catheter Tip Location. Issue 2 (1st March 2003) - De Biasi, Patrick; Lupescu, Radu; Burgun, Gilles; Lascurain, Pablo; Gaertner, Elisabeth
Abstract : Background and Objectives: The purpose of this article is to document where a lumbar plexus catheter introduced by the posterior approach will track and to evaluate the benefit of using systematic radiographic verification of catheter placement. Methods: A continuous lumbar plexus block (CLPB) by the posterior approach was performed on 169 consecutive adult patients scheduled for major hip, thigh, or knee surgery. Each catheter was verified by radiography using 10 mL contrast medium. The correct position of the catheter showed a caudally and laterally oriented contrast spindle. Results: Epidural spread of the contrast medium occurred in 3 of 169 patients (1.8%). Only 1 patient had a clinically relevant epidural spread of local anesthetic. Successful block of the lumbar plexus was achieved in the other 166 cases. Conclusions: Epidural spread of local anesthetic during lumbar plexus block should be expected to be relatively common. It can be easily identified clinically with fractionated doses of local anesthetic. The catheter tip was identified in the epidural space by radiographic verification in only 1.8% of cases. This expensive procedure is therefore unnecessary except when an unusual location is suspected, but not necessary to confirm a catheter assumed to be correctly positioned.